Impact of industrial yeast derivative products on the modification of wine aroma compounds and sensorial profile. A review. (1st October 2021) - Rigou, Peggy; Mekoue, Julie; Sieczkowski, Nathalie; Doco, Thierry; Vernhet, Aude
Highlights: YDPs contains aroma compounds that can be released during the wine making process. YDPs impact the wine sensorial profile. YDPs contains macromolecules that can interact with the aroma compounds. Mannoproteins may interact the most with the aroma compounds. Wine composition, pH and temperature modulate impact of YDPs on its aromatic profile.